7 - As questões dos Direitos Humanos na im-prensa escrita cabo-verdiana entre 2008 e 2009 : os casos dos jornais A Semana e Expresso das Ilhas - Redy Wilson Lima (Africa Media Review, 2012)
This article examines the coverage of the issue of human rights in two private weeklies in Cape Verde, “A Semana” and “Expresso das Ilhas” between the years 2008 and 2009. Content analysis, linking quantitative and qualitative data, focusing particularly on the activities of youth gangs, through editorials shows that the press actually attracts the readers’ attention on issues of human rights violations, but they are still covered superficially.